Pemanfaatan Media Youtube Dakwah Ustadz Adi Hidayat dalam Pengembangan Materi Fikih Madrasah Ibtidaiyah - Guntur Cahyono (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2019)
Social media are beneficial not only to communicate interpersonally but also to preach and educate people. One of these media is YoutubeÂ that can be applied in developing learning materials by capitalizing online preaching of IslamÂ teachers (ustadz) uploaded in this medium. This research gives description on how Youtube is useful as part of learning material development. In this research, the description reveals the facts that teachers employ not only text books or student work books (LKS) in material development but also online videos. Youtube videos of ustadzAdiHidayat can be used to develop Islamic principal (Fiqh) learning materials in Islamic elementary schools by downloading those videos. Teachers are required to be savvy in operating internetÂ media in learning material development for teaching and learning process.